Phosphorylation by casein kinase II affects the interaction of caldesmon with smooth muscle myosin and tropomyosin. - Bogatcheva, N V (1993)
Smooth muscle caldesmon was phosphorylated by casein kinase II, and the effects of phosphorylation on the interaction of caldesmon and its chymotryptic peptides with myosin and tropomyosin were investigated. The N-terminal chymotryptic peptide of caldesmon of molecular mass 27 kDa interacted with myosin. Phosphorylation of Ser-73 catalysed by casein kinase II resulted in a 2-fold decrease in the affinity of the native caldesmon (or its 27 kDa N-terminal peptide) for smooth muscle myosin. At low ionic strength, caldesmon and its N-terminal peptides of molecular masses 25 and 27 kDa were retarded on a column of immobilized tropomyosin. Phosphorylation of Ser-73 led to a 2-4-fold decrease in the affinity of caldesmon (or its N-terminal peptides) for tropomyosin. Thus phosphorylation of Ser-73 catalysed by casein kinase II affects the interaction of caldesmon with both smooth muscle myosin and tropomyosin.